THE PATHOLOGY OF THE SACROILIAC JOINT IS AN INTERDISCIPLINARY PROBLEM. NEUROLOGIST’S VIEW - Перевощикова, Нина Константиновна; Давиденко, Инна Владимировна (Medicine in Kuzbass, 2021)
Pain in the lower back is the most common complaint of patients in outpatient practice. Differential diagnosis is difficult, especially in the diagnosis of sacroiliac joint pathology (CPS). Difficulties in diagnosing sacroiliac joint dysfunction (pathology) explain the difficulties and errors in the treatment and prognosis of the disease. Among the total number of patients who passed through the neurological department of the day hospital of the Department Hospital at the Kemerovo station of JSC Russian Railways for 2.5 years (4658 people), patients with a diagnosis of ICD M42.1 – «Osteochondrosis» (cervical, thoracic, lumbar, sacral) made up 38 % (1677 people). Patients with a diagnosis of «Lumbar osteochondrosis with sacroiliac joint syndrome» were 135 people, the vast majority-women (64.4 %), the dysfunction of the CPS in which was mainly associated with pregnancy and childbirth. Every third of the observed women was aged 21-39 years, which indicates the need to improve the early diagnosis of CPS dysfunction in the postpartum period and rehabilitation to prevent the chronization of the process.